COMMON RISK FACTORS ASSOCIATED WITH OSTEOPOROSIS AND TOOTH LOSS - Alex, Aleena; Priyadharsini J, Vijaya shree; Prathap, Lavanya (International Journal of Psychosocial Rehabilitation, 2025)
Osteoporosis is a systemic skeletal disease characterized by low bone mass and bone tissue deterioration with a consequent increase in bone fragility and susceptibility to fracture. Low bone mineral density [BMD], age and low body mass index have been found to be major risk factors for osteoporosis. Periodontitis presents as a pathological loss of periodontal ligaments and alveolar bone resorption. The disease develops due to complex interactions between microbes and exaggerated immune response. Since both the diseases have a convergent mechanism leading to tissue destruction, investigation of the common markers would enable early diagnosis of the diseases. The aim of the present study was to identify these common inflammatory markers associated with osteoporosis and tooth loss by text-mining process. Furthermore, the brief review throws light on the underlying mechanisms behind the development of the disease, its management, treatment and prevention options. An extensive review of literature was carried to locate studies relating world-wide prevalence of osteoporosis and its association with tooth loss and other oral problems.